Pengembangan Sistem Informasi Data Pendeta Gereja Toraja Berbasis Web Menggunakan Framework Laravel - Genota Pali' Allo Linggi (JATISI, 2025)
Gereja Toraja is one of the Protestant church denominations in Indonesia, organized under a presbyterial-synodal structure, and spread across 17 provinces with thousands of congregants and hundreds of active pastors. The complexity of its administration and pastor data management requires an efficient, integrated, and accurate system. This study aims to develop a web-based pastor data management information system for the Gereja Toraja using the Laravel framework. The system is designed to facilitate real-time recording, updating, and reporting of data, replacing manual methods that are prone to duplication and data loss. Development follows the Waterfall model through requirements analysis, literature review, system design using UML, implementation, and testing with User Acceptance Test (UAT) techniques. The results indicate that the system improves administrative efficiency, data accuracy, and accessibility for both administrators and pastors. This system provides an effective solution for real-time and structured pastor data management in the Gereja Toraja.